Penerapan Fiqih Wudhu dan Shalat di MTs NU Kraksaan Probolinggo: Studi tentang Pemahaman dan Pengamalannya di Kalangan Siswa - Rusdiana, Rusdiana; Rodhiyya Aluf, Zulfa; Mahbubi, M. (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
This study aims to explore the understanding and practice of wudhu (ablution) and shalat (prayer) among 7th-grade students at MTs NU Kraksaan Probolinggo, as part of fiqih education, which plays a vital role in shaping students' religious character. The research employed a qualitative descriptive approach. Data were collected through in-depth interviews with students and teachers, direct observation of worship activities, and documentation of fiqih learning materials used in class. The findings reveal that most students possess a basic understanding of the procedures for wudhu and shalat, but a significant gap remains in actual practice—particularly regarding the accuracy of implementation and the internalization of the spiritual meaning behind the rituals. Factors such as home prayer habits, time constraints, and limited opportunities for hands-on practice at school contribute to this gap. On the other hand, Islamic religious education teachers have delivered the material systematically, but challenges persist in ensuring students’ emotional engagement and consistent practice beyond the classroom. This study provides a theoretical contribution to the development of fiqih education at the Madrasah Tsanawiyah level by emphasizing the importance of integrating cognitive, affective, and psychomotor aspects in worship education. Practical recommendations include increasing hands-on practice during fiqih lessons, creating a school environment that supports regular prayer, and encouraging active parental involvement in guiding religious practice at home. Collaboration among teachers, schools, and families is key to cultivating correct, consistent, and meaningful religious habits in students